The Application of the Contributory Negligence Doctrine in Determining Bank Liability for Customer Losses - Made Yoga Keysa Wira Gandhi; Made Aditya Pramana Putra (IJBLE Scientific Publications Community Inc., 2026)
This article examines the legal consequences of applying the contributory negligence doctrine to bank liability for customer losses arising from errors, negligence, or misconduct committed by bank employees. The central issue is whether a bank, as a financial services business actor, may rely on customer fault to exclude liability even when the loss is causally connected to employee conduct performed within the bank's operational sphere. Using normative legal research, this article applies statutory, conceptual, and case approaches to Indonesian civil law, banking regulation, financial consumer protection norms, and selected court decisions. The analysis focuses on Article 10 of Financial Services Authority Regulation Number 22 of 2023 on Consumer and Public Protection in the Financial Services Sector, the Indonesian Civil Code, the Banking Law, and relevant dispute-resolution mechanisms. The findings indicate that banks bear prima facie responsibility for losses caused by employees, directors, commissioners, or third parties acting on behalf of the bank. Article 10(2), which allows financial services providers to avoid liability when consumer involvement or negligence is proven, functionally resembles contributory negligence. However, an absolute or all-or-nothing application of that provision is difficult to reconcile with the structural imbalance between banks and customers, the prudential principle, and modern financial consumer protection standards. The article argues that Indonesian banking liability should be interpreted through a proportional model closer to comparative negligence, so that customer fault may reduce but should not automatically extinguish bank liability where employee negligence remains a substantial cause of loss.